Protocols Play a Crucial Role in Bio Psychosocial Assessment of Patients by Staff Nurses- A Methodological Explanation (Medico Legal Update, 2019)
Use of protocols in various nursing care activities do enhance the performance of nurses. This study wasconducted with the aim of evaluating the effectiveness of the protocol on bio-psychosocial assessmentof patients among the staff nurses in the general wards of a selected hospital. An evaluative approachwas used to measure the effectiveness of the protocol on bio-psychosocial assessment of patientsamong the psychiatric nurses. The study was held among 60 staff nurses chosen by non-probabilitypurposive sampling, who were working in the General ward of Father Muller Medical College hospital,Mangalore, India, on 60 admissions to the same general wards of the same hospital. The results revealedthat post –interventional practice has increased from Day1 to Day5. The data demonstrated thatthere was a significant change in practice day by day. Participants have shown a great improvementin the bio-psychosocial assessment of the patients and 80% of the nurses accepted the procedure.